Evaluation of a Multiplex PCR for Detection of the Top Seven Shiga Toxin-Producing Escherichia coli Serogroups in Ready-to-Eat Meats, Fruits, and Vegetables. (23rd November 2019) - Gao, Anli; Fishcher-Jenssen, Jennifer; Cooper, Colin; Li, Honghong; Li, Jiping; Chen, Shu; Martos, Perry
Abstract: Background : Ready-to-eat (RTE) meats, fruits, and vegetables contaminated by Shiga toxin producing Escherichia coli (STEC) raise serious concerns because they are often consumed directly without further processing. Objective: To evaluate a multiplex PCR for the detection of STEC across food categories. Methods: Samples (25 g) from seven RTE meat and nine fruit and vegetable matrices were inoculated with each of seven STEC (O157:H7, O26, O121, O145, O45, O103, O111) strains targeting 10 CFU/25 g, enriched in 225 mL of modified tryptone soya broth (mTSB), and tested by a multiplex real-time PCR for stx and eae genes, following U.S. Department of Agriculture (USDA) Food Safety and Inspection Service (FSIS) Microbiology Laboratory Guidebook (MLG) 5B, which was originally validated for meat products and environmental sponge. Results: The mTSB was successful at enriching for STEC in RTE meat, fruit, and vegetable matrices, except for sprouts; however, mEHEC resulted in successful enrichment of target organisms in mung bean sprouts. Suppression of eae results by stx in PCR was observed in six fruit and vegetable matrices. Conversely, suppression of stx gene by eae was not observed. PCR solely targeting eae is recommended if a fruit or vegetable sample tested positive for stx and negative for eae . Despite the significant effect from food matrix, strain, and experimental batch, the cycle threshold of PCR was <30 in inoculated samples, and mostly 30–42 and up in uninoculated samples. Conclusions: The multiplex PCR can be adopted for detection of all seven regulated STEC in RTE meat, fruit and vegetable matrices after validation with cut off value selected and justified based on real samples.